Revealing students' critical thinking ability according to facione's theory - Mastuti, Ajeng Gelora; Abdillah, Abdillah; Sehuwaky, Nurlaila; Risahondua, Ratna (Universitas Islam Raden Intan Lampung, INDONESIA, 2022)
The importance of critical thinking ability in solving mathematical problems can improve the quality of thinking and make thinkers better understand the content that has been studied. This research aims to reveal students' critical thinking ability using Facione's theory to solve comparative problems. The research method used in this research is descriptive qualitative. The subjects of this study consisted of 2 students taken from 20 participants based on data saturation. Data collection techniques used in this study were tests, interviews, validation sheets, and documentation. The data analysis technique of the research results was carried out through three stages: data reduction, data presentation, and drawing conclusions. Based on the discussion results, the researcher revealed students' critical thinking skills through six components of critical thinking based on Facione's theory, namely Interpretation, Analysis, Evaluation, Inference, Explanation, and Self-Regulation. Significant differences between the two subjects appear at the explanation stage. At this stage, subject 1 uses the procedure in the concept scheme, and the explanation of the argument of subject 1 is very logical. This can be seen in clarifying the evaluation and inference stages, where the subject performs calculations correctly and logically. Meanwhile, subject 2 uses detailed procedures in its planning, indicated by notes at the analysis stage.